Ergodic capacity of MIMO channel with and without channel state information - Lykhograi, Vasil; Vovchenko, Victoria; Nooh Taha, Nasif (Видавництво Львівської політехніки, 2012)
This report contains the results of modeling the ergodic capacity (EC) of the data transmission digital systems (DTDS) in the medium with multiple input - multiple output (MIMO) at presence and absence of information about the channel state information (CSI).
Keywords: Ergodic capacity; MIMO; antenna arrays